Case Report: A Case of Pituitary Adenoma Producing Growth Hormone and Thyroid-Stimulating Hormone Simultaneously - Sanada, Junpei; Tatsumi, Fuminori; Kamei, Shinji; Fushimi, Yoshiro; Shimoda, Masashi; Kohara, Kenji; Nakanishi, Shuhei; Kaku, Kohei; Mune, Tomoatsu; Kaneto, Hideaki (Frontiers in Endocrinology, 2021)
Background: Pituitary adenoma producing growth hormone (GH) or thyroid-stimulating hormone (TSH) is characterized by various specific symptoms and/or findings. However, the frequency of pituitary adenoma producing both hormones is relatively low. In this report, we show a case of pituitary adenoma producing both GH and TSH simultaneously. Case presentation: A 27-year-old woman was diagnosed as acromegaly based on various symptoms and clinical findings. For further examination and treatment, she was hospitalized in our institution. It was likely that this subject had pituitary adenoma producing both GH and TSH. In brain magnetic resonance imaging, there was a giant tumor around pituitary fossa. After the diagnosis of GH- and TSH-producing pituitary adenoma, pituitary tumor resection and cyber knife therapy were performed. In addition, we started additional treatment with somatostatin analog and GH receptor antagonist. After then, GH and IGF-1 levels were suppressed. After the operation, since thyroid function was not sufficiently suppressed, we started anti-thyroid drug thiamazole. After then, thyroid function was normalized and we stopped thiamazole. In GH and TSH staining, many GH-positive and TSH-positive cells were observed. These findings further confirmed our diagnosis that the pituitary adenoma in this subject produced both GH and TSH simultaneously. Conclusions: We should bear in mind the possibility of pituitary adenoma producing both GH and TSH at the same time.